2011
DOI: 10.1088/0022-3727/44/43/435402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of temperature threshold for melt surface deformation during laser interaction on iron at atmospheric pressure

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. . It is thus essential to estimate the recoil pressure in order to describe physical processes or to carry out numerical simulations. However, there exists no quantitative estimation of the recoil pressure near the boiling temperature (T v ), which is particularly important in welding process. In this study we experimentally investigated the recoil pressure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 33 publications
0
42
1
5
Order By: Relevance
“…[8][9][10][11] At high welding speed the surface of the liquid metal on the front wall of the keyhole is covered with small ripples or step like structures. With the help of a streak imaging technique developed by the authors [12] the velocity of these ripples has been measured and found to be in the order of 5-20m/s.…”
Section: Flow Desciptionmentioning
confidence: 99%
“…[8][9][10][11] At high welding speed the surface of the liquid metal on the front wall of the keyhole is covered with small ripples or step like structures. With the help of a streak imaging technique developed by the authors [12] the velocity of these ripples has been measured and found to be in the order of 5-20m/s.…”
Section: Flow Desciptionmentioning
confidence: 99%
“…This model contains all physical processes described previously and was used for the laser welding in [33], for the laser cutting [16] and for the laser drilling in [5,23] and [31]. The output of this 1D model are the drilling velocity, the ejection melt velocity and the surface temperature but only at a steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this assumption was proposed nearly 40 years ago and widely adopted in modeling studies, 24,[29][30][31][32] it was only recently experimentally validated by some of the authors of this paper. 21 Their experimental demonstration challenges the well-known assumption of Semak and Matsunawa 33,34 that the keyhole temperature does not need to exceed the boiling point to support the opening of the keyhole during LW under atmospheric pressure. With the proposed ambient pressure dependent surface pressure model shown in Eq.…”
Section: Resultsmentioning
confidence: 95%
“…(1). 21 Moreover, it was also demonstrated that strong evaporation occurs in laser welding, only when the temperature of irradiated surface exceeds the boiling point of material. 21 Bearing these facts in mind, an improved model of recoil pressure for LW process under any ambient pressure p amb can be proposed, as shown in Fig.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation